Hiding the Vector Resonance Signal Hiding the Vector Resonance Signal - Mikulas Gintner; Josef Juran (Communications - Scientific letters of the University of Zilina, 2014)
We investigate how the interplay of the direct and mixing-induced couplings of the hypothetical SU(2)L+R vector triplet resonance to the third quark generation can hide the resonance signal in ,tb tb , and / bt tb channels. The vector resonances are assumed to represent bound states of hypothetical strongly-interacting new physics, the extension of the Standard model.